'Small Forms' and Large: the Russian Case at the Golden Mask, 2019. (August 2019) - Shevtsova, Maria
Abstract : Every year at the Golden Mask National Theatre Award and Festival in Moscow, the Russian Case has its special characteristics, and 2019 clearly reflected the selection made by the many critics who travel far and wide across Russia to choose shows for the Festival. In this overview Maria Shevtsova gives some idea of the work in the category generally described as 'small forms', which dominated the Russian Case, and breaks the category down into the different genres gathered under its name. She also refers to several productions that are 'large forms', notably those directed by Konstantin Bogomolov and Yury Butusov, who are major directors in the field acclaimed nationally and internationally. Shevtsova's The Cambridge Introduction to Theatre Directing (2014, co-authored) is a landmark in research on European directors and her Rediscovering Stanislavsky is forthcoming (2019). She is co-editor of New Theatre Quarterly.